DNA Damage, Oxidative Stress and Related Metabolic By-Products in Cancer and Environmental Studies - Peluso, Marco E. M.; Galli, Andrea; Mello, Tommaso; Peluso, Marco E. M.; Galli, Andrea; Mello, Tommaso (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Computational fluid dynamics (CFD), which uses numerical analysis to predict and model complex flow behaviors and transport processes, has become a mainstream tool in engineering process research and development. Complex chemical processes often involve coupling between dynamics at vastly different length and time scales, as well as coupling of different physical models. The multiscale and multiphysics nature of those problems calls for delicate modeling approaches. This book showcases recent contributions in this field, from the development of modeling methodology to its application in supporting the design, development, and optimization of engineering processes.
English
Keywords: Technology: general issues; wood dust; nasal epithelia; VOCs; M1dG; reactive oxygen species (ROS); nucleotide excision repair (NER); base excision repair (BER); oxidative DNA damage; DNA damage response and repair network; immune response; autoimmunity; systemic lupus erythematosus; systemic sclerosis; rheumatoid arthritis; oxidative stress; abasic sites; chromatin organization; apoptosis; DNA damage; general anesthesia; neuraxial anesthesia; comet assay; chronic myeloid leukemia; genetic instability; DNA double-strand breaks; DNA damage response; benzo[a]pyrene; BPDE-DNA adduct; silymarin; detoxification; Nrf2; PXR; DNA repair; base excision repair (BER)glycosylases; colorectal cancer; reactive oxygen species; metabolic adaptation; drug resistance; cancer; thyroid; thyroid cancer; volcano; metals; metallome; carcinogens; hormesis; environment pollution; metal biocontamination; n/a; Diamond-Blackfan anemia; 8-oxoguanine; inflammatory cytokines; erythrocyte lifespan